The present and future of digital health, digital medicine, and digital therapeutics for allergic diseases - He Zhang; Yang Cao; Haibo Jiang; Qilin Zhou; Qintai Yang; Lei Cheng (Clinical and Translational Allergy)
Abstract Background Digital health, digital medicine, and digital therapeutics integrate advanced computer technologies into healthcare, aiming to improve efficiency and patient outcomes. These technologies offer innovative solutions for the management of allergic diseases, which affect a significant proportion of the global population and are increasing in prevalence. Body This review examines the current progress and future potential of digital health in allergic disease management. It highlights key advancements, including telehealth, mobile health (mHealth), artificial intelligence, clinical decision support systems (CDSS), and digital biomarkers, with a focus on their relevance to allergic disease management. The role of digital tools in improving treatment adherence, enabling remote care, and integrating environmental and patient data into personalized care models is discussed. Challenges such as data privacy, interoperability, and equitable access are addressed, alongside potential strategies to overcome these barriers. Conclusion Digital therapy will play an important role in allergic diseases, and the further development of digital therapies will effectively promote the development of clinical research, digital biomarkers, hypoallergenic environments and digital twins. More research is needed to support the progress of digital therapy for allergic diseases.